(3eYLe GdHdOGf aj eYQaI GdeOf hGdbQi hGdNQGH hGdYeGQ hGdSgd hGdhYQ ef cd ecGfs - (3jGbhJ Hf YHO Gddg GdQhej GdMehj, TgGH GdOjf CHh YHO Gddg,J (B626 (3g` s
(3ChdgG (B:s
(3MdGMd s
(3BNQgG (B:s
(3OjhQI s
(3GdfSNI HgG MhGTs
(3Ydjg NW GdYdGeI GdUaOis
(3ef GdfSNI faSgGs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdLZQGajG h GdHdOGfs